Entrepreneurial activity in veterinary medicine is the basis of veterinary service - B. M. Kurtiak; M. S. Romanovych; O. P. Rudenko; Z. A. Guta; M. M. Romanovych (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
For more than a quarter of a century, the transformation of the agro-industrial sector of the economy of Ukraine (as well as other sectors of the economy) has been taking place under market conditions. These changes directly concern both animal husbandry and the veterinary medicine industry. The ownership system, gene pool and number of animals, herd structure, breed characteristics, etc. are changing. Accordingly, the requirements for the range and quality of veterinary services are changing. Practically, our country's initial market relations stage in veterinary medicine has been completed. At present, all the necessary components of the veterinary market exist: private property; the absence of a centralized distribution and supply system; a set of existing and potential buyers (consumers); a set of competing sellers (suppliers) of veterinary goods and services. Today, the labor market for veterinary medicine specialists has also begun to operate (replacing state employment). There are many unemployed veterinary specialists. One of the essential reasons for this phenomenon is the unpreparedness of young specialists to work in market conditions. To work successfully in the market system, it is not enough to have only veterinary professional knowledge; additional knowledge of market economics, entrepreneurship, finance, legislation, management and marketing, psychology, etc., is necessary. The main direction and ultimate goal of reforming the agrarian sector of our country's economy, which directly concerns the veterinary medicine service, is to provide a complex of veterinary services to animal owners. To solve this problem, Ukraine envisages reorganizing the network of state veterinary medicine institutions so that a veterinary service point would operate in the territory of each village council and, in the future, in each large settlement. Providing veterinary services under licenses forces veterinary medicine specialists to master the basics of entrepreneurship and market laws, better organize their work, and build relationships with colleagues and animal owners following modern requirements. Some answers to these questions are highlighted in the presented article.